Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/jmv.24093
|View full text |Cite
|
Sign up to set email alerts
|

HIV transmission and related risk factors among serodiscordant couples in Liuzhou, China

Abstract: To evaluate the incidence and risk factors for human immunodeficiency virus (HIV) seroconversion of HIV-negative partners among HIV-discordant couples in Liuzhou, China, 1854 eligible HIV-serodiscordant couples were retrospectively identified through the HIV epidemiology and follow-up database from January 1, 1996 to June 30, 2013. Cox proportional-hazards model was used to examine risk factors related to HIV seroconversion of negative partners. Finally, 125 HIV seroconversion occurred over 4963.5 person-years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Carcinogenic HPV persistent infection is the most important reason for the progression of HPV-related anogenital cancers. 23 Therefore, the sex difference in the incidence of anal cancer in Liuzhou could not represent the overall sex trend of China and might be more similar to sexually active trends in developed countries in which women have higher incidences of anal caner than men. 22 Our data indicated that HPV 16 infections were more persistent in females than in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinogenic HPV persistent infection is the most important reason for the progression of HPV-related anogenital cancers. 23 Therefore, the sex difference in the incidence of anal cancer in Liuzhou could not represent the overall sex trend of China and might be more similar to sexually active trends in developed countries in which women have higher incidences of anal caner than men. 22 Our data indicated that HPV 16 infections were more persistent in females than in males.…”
Section: Discussionmentioning
confidence: 99%
“…17 Zhang et al reported that the HIV incidence among HIV-discordant couples of Liuzhou city is higher than the national level. 23 Therefore, the sex difference in the incidence of anal cancer in Liuzhou could not represent the overall sex trend of China and might be more similar to sexually active trends in developed countries in which women have higher incidences of anal caner than men. 24,25 Because few anal cancer cases were reported each year in Liuzhou, we could not sufficiently directly analyze the difference in incidences between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Liuzhou is a city with the highest prevalence of HIV infection in Guangxi Zhuang Autonomous Region which has the second-largest number of people living with HIV in south central China (17). And MSM ranked the second place among the number of newly identi ed HIV/AIDS cases in Liuzhou city (18).…”
Section: Introductionmentioning
confidence: 99%
“…To control for differences in exposure to infection, studies have restricted their population to individuals known to have been exposed to infection. For instance, studies examining risk factors of HIV transmission have used populations of serodiscordant couples [38, 39], where the uninfected partner is known to be exposed. However, such studies are rarely performed for other STIs, as they are costly and methodologically challenging (difficult to adequately condition on exposure to infection).…”
Section: Discussionmentioning
confidence: 99%